Pengaruh Desentralisasi Fiskal, Belanja Modal, dan Investasi Swasta Terhadap Indeks Pembangunan Manusia - Pramartha, I Made Aditya; Dwirandra, A. A.Ngurah Bagus (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
The purpose of this study is to prove empirically about the effects of fiscal decentralization, capitalexpenditure, and private investment on the human development index. This research was conducted in all regencies / cities in Bali Province. The population used was all of the data on Region Budget Realization Report and Human Development Index in all regencies / cities in Bali Province in 2011-2016. The sampling method used was saturation.The research data was processed using multiple linear regression analysis technique. The results of this study proves empirically that fiscal decentralization and private investment had a significant positive effect on Human Development Index. Capital expenditure did not have an effect on Human Development Index. Keywords : Fiscal decentralization, capital expenditure, private investment, human  development inde